2018
DOI: 10.1292/jvms.17-0590
|View full text |Cite
|
Sign up to set email alerts
|

First report of the occurrence and whole-genome characterization of <i>Edwardsiella tarda</i> in the false killer whale (<i>Pseudorca crassidens</i>)

Abstract: Although several Edwardsiella tarda infections have been reported, its pathogenic role in marine mammals has not been investigated at the genome level. We investigated the genome of E. tarda strain KC-Pc-HB1, isolated from the false killer whale (Pseudorca crassidens) found bycaught in South Korea. The obtained genome was similar to that of human pathogenic E. tarda strains, but distinct from other Edwardsiella species. Although type III and VI secretion systems, which are essential for the virulence of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…To resist phagocyte-mediated killing, various essential strategies, such as enzyme production including CAT, POD, and SOD, have been implicated by E. tarda to neutralize reactive oxygen species (ROS), while TTSS and T6SS contribute to invasion and subversion of the host cells (46). In the present study, 129 T3SS genes were predicted; however, in a previously reported E. tarda KC-Pc-HB1, no T3SS/T6SS genes were detected (41), indicating that SC002 is a more virulent strain.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…To resist phagocyte-mediated killing, various essential strategies, such as enzyme production including CAT, POD, and SOD, have been implicated by E. tarda to neutralize reactive oxygen species (ROS), while TTSS and T6SS contribute to invasion and subversion of the host cells (46). In the present study, 129 T3SS genes were predicted; however, in a previously reported E. tarda KC-Pc-HB1, no T3SS/T6SS genes were detected (41), indicating that SC002 is a more virulent strain.…”
Section: Discussioncontrasting
confidence: 83%
“…Unlike the published Edwardsiella complete genomes having one or two plasmids, the SC002 genome contained four novel plasmids ( 34 , 37 39 ). Subsequently, BLAST analysis shows that the pEtSC002-1 was identical to the S. enterica plasmid (NZ_CP037959.1), while pEtSC002-2, pEtSC002-3, and pEtSC002-4 were identical to the E. tarda KC_PC_HB1 plasmid (NZ_CP023707.1) ( 40 , 41 ). The antibiotic resistance determinants were only observed on pEtSC002-1 where the resistance gene patterns ( sul1, sul2, cml, tetA, aph33 , and aph6 ) were similar to those of EIB202 plasmid resistome ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is considered to include potential pathogens to humans and animals ( 52 , 66 ), in the present study, its high abundance was not related to any pathogenies in the two pups. Edwardsiella has been associated with diseased cetaceans ( 67 ) while pathogenic species, like Edwardsiella tarda , have been isolated from non-diseased animals ( 48 , 68 , 69 ). This bacterium could be a threat for the released pups, as its abundance seemed to increase toward the end of the rehabilitation period.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with the pan-susceptible phenotypic AST profile of our isolate. The E. tarda KC-Pc-HB1 reference strain was initially isolated from the blood of a false killer whale ( Pseudorca crassidens ), a tropical and warm temperate dolphin species, that had been caught along the South Sea (Republic of Korea) ( Lee et al., 2018 ).…”
Section: Diagnostic Assessmentmentioning
confidence: 99%